Marion Glass Banister papers - Banister, Marion Glass, 1868-1951.
Chiefly correspondence together with biographical material, memorabilia, and other papers documenting Banister's service as U.S. assistant treasurer. Includes items relating to the Democratic National Committee. Correspondents include her brother, Carter Glass, and her sister, Meta Glass.
U.S. assistant treasurer, editor, and Democratic Party leader.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Glass, Carter, -- 1858-1946 -- Correspondence; Glass, Meta, -- 1880-1967 -- Correspondence; United States. -- Department of the Treasury; Democratic National Committee (U.S.); Democratic Party (U.S.); Editors; Public officials